EDUKASI BAHAYA ROKOK PADA REMAJA MTsS THAWALIB PADANG DI KECAMATAN KURANJI KOTA PADANG - Melisa Yenti; Hamidatul Yuni; Haniffazulhijjah Haniffazulhijjah; Irsyah Dunnas Jamka (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
According to the Global Youth Tobacco Survey (YGTS), there has been an increase in teenage smokers aged 13-15 years in the last five years, from 18.2% in 2014 to 19.2%. The survey results also show that adolescents are exposed to various media advertisements and quickly access cigarettes. Cigarettes contain highly addictive substances that can cause addiction and negatively impact adolescents' health and future. MTsS Thawalib Padang Islamic Boarding School has never received education regarding the dangers of smoking, and there are also cases of students smoking. This activity aims to increase knowledge and motivate youth not to smoke. Thawalib Padang. The target audience for this activity is all male students in Islamic boarding schools. The methods used are counseling, poster installation, and distribution of cigarette books. The activity was carried out by a team of lecturers and students from the Faculty of Public Health, Andalas University, which 75 students attended. After the activities were carried out, there was an increase in the average level of knowledge before (pre-test) counseling from 10.00 to 11.92 after (post-test) counseling with a p-value of 0.000. It can be concluded that there is an increase in knowledge after smoking-related education. It is hoped that students will be aware of the dangers of smoking and that students will be motivated not to smoke or smoke. It is also hoped that MTsS Thawalib Padang Islamic Boarding School will enforce a smoking-free area and strictly supervise students who smoke.